D. H. Lawrence's queer flatness. Issue 9 (2nd September 2022) - Masud, Noreen
ABSTRACT: Despite Lawrence's well-documented interest in 'Alpine' landscapes, characters in his Sons and Lovers (1913), The Lost Girl (1920) and Kangaroo (1923) find themselves lingering in and on flat spaces. This essay attends to the dynamics of these flat spaces to complicate critical models which have emphasised sympathy, vitality and responsiveness in encounters with the Lawrentian Other. It finds that in Lawrence's prose, physical flatness offers a mode of habitation, and an occasion for a literary style, which encode a reserved self-presentation, a failure of mutuality and sympathy, and a refusal to participate in an economy of responsiveness. The first section examines the stakes of Lawrence's peculiar insistence that the reader invests in characters and situations which will later vanish from the plot, refusing stable focal points in the novel's narrative landscape. The second section investigates the relationship between protagonist and flat landscape in Kangaroo to uncover a fundamental Lawrentian trope: openness which is nevertheless inaccessible, demanding a sustained attention that it cannot justify. The essay ends by arguing for the importance, in Lawrence, of relationship which may be at once intense and unresponsive, with one or more of the entities involved flatly complete in themselves.